CARDIORESPIRATORY AND HEMATOLOGICAL PARAMETERS OF HEALTHY FRENCH BULLDOGS (Colloquium Agrariae. ISSN: 1809-8215, 2021)
Brachycephalic dogs have a normal lower jaw and a receded upper jaw, and these dogs are predisposed to nostril stenosis, elongated palate, tracheal hypoplasia and hyperthermia due to heat stress. Given these characteristics, these dogs are more predisposed to respiratory and cardiovascular disorders. The popularity of brachycephalic dogs that have a greater tendency for cardiorespiratory disorders, such as French bulldogs, has increased recently; however, studies on the cardiorespiratory and haematological parameters in this breed are lacking. Thus, the present study sought to evaluate the cardiorespiratory and haematological parameters of healthy French bulldogs to standardize normal values and to serve as a basis for routine clinical, surgical and laboratory parameters and future studies on the breed. Thirty-six French bulldogs were used without predilection for age or sex, and the following parameters were evaluated: temperature (T), heart rate (HR), respiratory rate (RR), erythrogram, leukogram, total plasma protein, plasmatic fibrinogen, blood platelet count, urea, creatinine, alkaline phosphatase (AP) and alanine aminotransferase (ALT). The mean and standard deviation were as follows: T°C (38.3±0.4), HR (111.1±27.0) beats per minute, RR (54.8±32.5) breaths per minute, erythrocyte count (7.3±1.2x106), haemoglobin (16.9±2.8 g/dL), haematocrit (48.9±7.7%), MCV (67.6±2.4 fL), MCH (23.3±0.7 pg), MCHC (34.6±0.8%), RDW-CV (9.3±0.9; 9.2-12.0%), total leukocytes (11009.7±2907.3/mm3), band neutrophils (250.0±260.4/mm3), segmented neutrophils (7094.4±2307.3/mm3), eosinophils (589.7±561.3/mm3), lymphocytes (2020.8±1457.5/mm3), monocytes (987.6±528.4/mm3), total plasma protein (6.9±0.5 g/dL), plasmatic fibrinogen (274.1±96.5 mg/dL), blood platelet count (366.4±88.5/mm3), urea (35.2±12.6 mg/dL), creatinine (0.8±0.2/mg/dL), AP (49.1±25.8U/L) and ALT (36.2±12.3U/L). The haematological parameters and heart rate were within the normal values for the species, but the respiratory rate values (54.8±32.5 breaths per minute) were greater than the normal average of 10 to 30 breaths per minute. We conclude that the haematological parameters and heart rate of healthy French bulldogs are within the normal limit for dogs; however, the respiratory rate is above reference values, reinforcing the notion that dogs of this breed, although healthy, exhibit an increased risk of respiratory disorders.